2014
DOI: 10.1093/jisesa/ieu103
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal, Fumigant, and Repellent Activities of Sweet Wormwood Oil and Its Individual Components Against Red Imported Fire Ant Workers (Hymenoptera: Formicidae)

Abstract: In total, 29 compounds from sweet wormwood ( Artemisia annua L.) oil were identified using gas chromatography–mass spectrometry. The five active components were d -camphor, linalool, cineole, α-terpineol, and l (−)-borneol. The effectiveness of A. annua oil, as well as d -camphor, linalool, cineole, α-terpineol, and l (−)-borneol, as fumigants, contact insecticides, and repellents, were tested on the red imported fire ant Solenopsis invicta Buren. The results indicated that A. annua oil has no significant topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…Many plant-based products were reported as being effective against fire ants (Appel et al, 2004;Cheng et al, 2008;Wang et al, 2012;Tang et al, 2013;Li et al, 2014;Wang et al, 2014;Zhang et al, 2014;Huang et al, 2016). The present study demonstrated that sweet flag powder is also an effective plant-based product that not only kills ants, but also repels them.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Many plant-based products were reported as being effective against fire ants (Appel et al, 2004;Cheng et al, 2008;Wang et al, 2012;Tang et al, 2013;Li et al, 2014;Wang et al, 2014;Zhang et al, 2014;Huang et al, 2016). The present study demonstrated that sweet flag powder is also an effective plant-based product that not only kills ants, but also repels them.…”
Section: Discussionsupporting
confidence: 62%
“…That similarity was also observed during this study. Huang et al (2016) and Zhang et al (2014) also found the similar effects on mortality of S. invicta by different bioactive compounds or essential oils during their study.…”
Section: Repellency Of the Bioactive Compounds In Sweet Flagsupporting
confidence: 53%
See 1 more Smart Citation
“…1,8-Cineole or eucalyptol, a monoterpenoid, is the main component of the volatile oils obtained from several plants and has many applications in the fields of flavour and fragrances, pharmacy. It also acts as insecticide and insect repellent [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2014) reported that linalool could absolutely kill minor workers at 5 mg/centrifuge tube within 24 h and 3 mg/centrifuge tube (48 h) after treatment. Few studies have reported on the insecticidal activity of caryophyllene.…”
Section: Discussionmentioning
confidence: 99%